THE ROLE OF IDIOMATIC EXPRESSIONS FOR ENGLISH LANGUAGE LEARNERS - B. Qaypova; U.Kalbaeva (Scholar Express Journal, 2022)
According to Boers in MED Magazine, all languages have idioms and are full of them. In each language native speakers tend to use idiomatic expressions because there are some situations or words that is mostly explained in figurative meaning to understand each other adequately. However, it is the natural phenomena that non-native speakers face challenges while learning language because they cannot even imagine what the idiomatic expression is mainly based on
Keywords: Idiomatic Expressions; Non-Native Speaker; Difficulties; Examples